Tiket.Com Customers Repurchase In The New Normal Era - Muh. Alvianto Putra Arizandi Sadarrudin; Yundi Permadi Hakim; Adi Sijanto (SEIKO : Journal of Management & Business, 2023)
The purpose of this study is to look at how online customer reviews and the calibre of electronic services affect repeat purchases both separately and simultaneously. In the city of Samarinda, the study was conducted. The sample size for this study is 71 respondents, and the demographics are customers who buy tickets through the online ticketing service Tiket.com. In this study, data were analysed using the validity test, reliability test, classic hypothesis test, multiple linear regression analysis, coefficient of determination test, F test, and t test. Keywords: On line consumer Reviews, E-Services Quality And Purchase Return.